Mobility during the Upper Palaeolithic in Greece: Some Suggestions for the Argolid Peninsula - Elefanti, Paraskevi; Marshall, Gilbert (Ex Novo: Journal of Archaeology, 2018)
The mobile hunting and gathering way of life has persisted for over 95% of human history. As ethnographic studies of recent societies have highlighted, mobility was key to the exploitation of the natural environment, while at the same time enabling groups to regulate their populations through fission and fusion. Combinations of mobility, technology and social networks enabled the near complete global spread of hunter-gatherers prior to the more settled farming way of life. Despite difficulties in extrapolating back in time from modern societies, their study can provide useful baseline indicators as to how settlement and subsistence was likely to have been organised during the Palaeolithic. The archaeological record as well as the seasonal variation in the natural environment, suggest that the fundamental challenges faced by groups during the Palaeolithic would have been broadly similar to those of today. Our study is based on three major cave sites in the Peloponnesian Argolid and applies the results of recent ethnographic studies to suggest ways in which the distribution of Upper Palaeolithic sites in the area can be understood. Our aim is threefold, to introduce mobility as the fundamental element of the huntergatherer way of life. To introduce the sites of Klissoura, Kephalari and Franchthi caves and finally, to consider how insights from modern societies can be applied to understand the Palaeolithic record of the Argolid.